PENGARUH KEBIASAAN KONSUMSI MAKANAN CEPAT SAJI DAN GAYA HIDUP KONSUMTIF TERHADAP PERILAKU PENGELOLAAN KEUANGAN MAHASISWA - Desti Nadia Tatalia; Dila Ratulangi; Andini Destiana Nazir; Firda Septiana (CV. Cendikiawan Muda Sriwijaya, 2026)
Changes in modern lifestyles have influenced students’ consumption patterns, including the increasing consumption of fast food and the tendency to adopt a consumptive lifestyle. These phenomena can affect students’ ability to manage their finances effectively. This study aims to analyze the influence of fast-food consumption habits and consumptive lifestyles on students’ financial management behavior. The research employed a quantitative approach, with fast-food consumption habits and consumptive lifestyle as the independent variables, and students’ financial management behavior as the dependent variable. The results indicate that fast-food consumption habits have a negative and significant effect on students’ financial management behavior. Students who consume fast food more frequently tend to spend a larger portion of their money on consumptive needs, which reduces their ability to manage finances effectively. Furthermore, a consumptive lifestyle also has a negative and significant effect on students’ financial management behavior. The tendency to follow trends, make purchases based on wants rather than needs, and be influenced by social environments and digital media makes it more difficult for students to control their spending and prioritize financial needs. Simultaneously, fast-food consumption habits and consumptive lifestyles were found to have a significant impact on students’ financial management behavior. Therefore, improving financial literacy, budgeting skills, and self-control in consumption patterns is essential for helping students achieve healthier, more stable, and well-planned financial conditions in the future.